What does the broken brain say to the neuroscientist? Oscillations and connectivity in schizophrenia, Alzheimer's disease, and bipolar disorder - Mathes, Birgit; Schmiedt-Fehr, Christina; Femir, Banu; Emek Savaş, Derya Durusu; Tülay, Elif; Tan, Devran; Düzgün, Aysel; Güntekin, Bahar; Özerdem, Ayşegül; Yener, Görsev G.; Başar Eroğlu, Canan; BAŞAR, EROL (Elsevier Science Bv, Po Box 211, 1000 AE Amsterdam, Netherlands, 2016)
The application of the concept and methods of brain oscillations has been an important research area in neurosciences. In the last decades, besides the application in cognitive processes, the study of changes in brain oscillations in diseases has also become an important focal point of research. In the present paper, some remarkable examples in three different diseases are taken into consideration: 1) schizophrenia (SZ), 2) Alzheimer's disease (AD), 3) bipolar disorders (BD). In the current literature, decreased oscillations in cortical recordings are observed in most of the pathologies. For example, decrease of gamma activity in SZ, decrease of delta activity in almost all diseases, as well as frequency shifts in alpha and the lower frequencies were recorded. However, there are also paradoxical cases in which an increase of oscillatory activities is observed. In BD, whereas alpha activity is greatly decreased, a huge increase of beta activity is observed. Or, in SZ, a paradoxical increase of gamma activity can be observed during cognitive loading. We also observed paradoxical changes in the analysis of connectivity. In AD, we find that alpha, delta, and theta coherences between distant parts of the cortex are greatly decreased, whereas in the gamma band, event-related coherences attain very high values. The comparison of the results and paradoxical changes in diseases may lead to important conclusions related to the web of oscillations and neurotransmitters. In turn, we could gain new insights to approach "brain function", in general. (C) 2016 The Authors. Published by Elsevier B.V.
Keywords: Oscillations; Connectivity; Schizophrenia; Alzheimer's disease; Bipolar disorder; Event-Related Oscillations; Mild Cognitive Impairment; Working-Memory; Resting State; Established Schizophrenia; Gamma-Oscillations; Euthymic Patients; High-Risk; Eeg; Responses